Fresh Graduate Students’ Difficulties in Writing Research Articles - Cindi Fitri; Wisma Yunita; Zahrida Zahrida (Edu-Ling: Journal of English Education and Linguistics, 2021)
Writing research article is one of requirement for a student’s university to be fulfilled before graduate. However, writing research article is not easy for the student. This research aimed to find out the difficulties in writing research article, the cause of the difficulties in writing research article and the way to overcome the difficulties in writing research article. The respondents of this research were 4 fresh graduate students who graduated in 2020 and the data ware obtained through interview. This research used descriptive qualitative method by using the procedures from Miles and Huberman (1994). The result of this study shows that the difficulties in writing research article were in finding references and struggle in using correct grammar, the worry about feedback from the readers was the cause of the difficulties and the fresh graduate had their own solution to overcome the difficulties in writing research article. In conclusion, the fresh graduate of the English Education Study Program of Bengkulu University faced various difficulties in writing research article and had cause of the difficulties in writing research article, but they had solution to deal with such difficulties.